2001
DOI: 10.1034/j.1600-6143.2001.010109.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Early Renal Transplant Protocol Biopsies – the High Incidence of Subclinical Tubulitis

Abstract: To investigate the possibility that we have been underestimating the true incidence of acute rejection, we began to perform protocol biopsies after kidney transplantation. This analysis looks at the one-week biopsies. Between March 1 and October 1, 1999, 100 adult patients undergoing cadaveric kidney or kidney/pancreas transplantation, or living donor kidney transplantation, underwent 277 biopsies. We focused on the subset of biopsies in patients without delayed graft function (DGF) and with stable or improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 14 publications
5
83
0
Order By: Relevance
“…No deaths were observed, and only one graft was lost; all complications presented within 4 h of biopsy (27). Similarly, of 277 renal biopsies that were performed in a single-center study, there was only one (0.4%) serious hemorrhagic complication (28). An additional study of 1171 protocol biopsies has reported rates of major complications of just 0.7% when a 16-gauge needle was used to perform the procedure and 1% when an 18-gauge needle was used (29).…”
Section: Safety Of Protocol Biopsiesmentioning
confidence: 91%
“…No deaths were observed, and only one graft was lost; all complications presented within 4 h of biopsy (27). Similarly, of 277 renal biopsies that were performed in a single-center study, there was only one (0.4%) serious hemorrhagic complication (28). An additional study of 1171 protocol biopsies has reported rates of major complications of just 0.7% when a 16-gauge needle was used to perform the procedure and 1% when an 18-gauge needle was used (29).…”
Section: Safety Of Protocol Biopsiesmentioning
confidence: 91%
“…Our current definition of subclinical rejection requires that the serum creatinine be increased by Ͻ10% 2 wk before the protocol biopsy and that the histologic Banff score is "ai2at2" (type IA acute rejection) or greater. Numerous groups since have confirmed the occurrence of subclinical rejection as defined above, in both adults (7)(8)(9)(10)(11)(12)(13)(14) and children (15,16). Some investigators include "borderline" rejection (Banff score Ͻai2at2) in the subclinical rejection category (7,9 -11,14).…”
Section: Subclinical Rejection: Prevalence Risk Factors and Signifimentioning
confidence: 92%
“…More recent studies have reported on early subclinical rejection in patients who received tacrolimus, either with (10,11,13,21,22) or without (7) MMF. Jurewicz (7) reported a prevalence of subclinical rejection (that included "borderline") of 18% at 3 mo in patients who received kidneys from deceased donors and were treated with tacrolimus, azathioprine, and prednisone.…”
Section: Prevalence Of Subclinical Rejectionmentioning
confidence: 99%
“…This discrepancy between clinical signs of renal failure and histologic findings of rejection confirms the finding in humans that renal allograft biopsies can diagnose subclinical rejection and are an important diagnostic tool for the follow up of renal transplants. 7,13,14,21,26,27 Although the Banff '97 classification was helpful for detecting a rejection, it did not reliably reflect the severity of the reaction. No significant differences were found in serum creatinine concentrations (used as measure for the severity of renal failure) in the different groups of the acute or active (P ϭ 0.942) or chronic (P ϭ 0.282) rejection reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In feline renal transplants, the incidence of distinct tubulitis, in which individual lymphocytes are found in the tubular wall or lumen, is low and difficult to ascertain, whereas in the Banff '97 classification system, tubulitis is one of the principal indicators of an acute cellular rejection. 23,27 The severity of this tubular inflammation forms the basis for the differentiation between renal tubulointerstitial rejection and inflammation character- ized as borderline changes (KDARB). Therefore, in this system, many feline renal transplants with distinct interstitial inflammation attributed to acute cellular rejection were not classified as such.…”
Section: Discussionmentioning
confidence: 99%